Nociceptive Response Is a Possible Marker of Evolution in the Level of Consciousness in Unresponsive Wakefulness Syndrome Patients - Cortese, Maria Daniela; Arcuri, Francesco; Nemirovsky, Idan E.; Lucca, Lucia Francesca; Tonin, Paolo; Soddu, Andrea; Riganello, Francesco (Frontiers in Neuroscience, 2021)
The Nociception Coma Scale (NCS) and its revised version (NCS-R) were used to evaluate behavioral responses to pain in non-communicative patients. We hypothesized that if patients demonstrate changes to their NCS(-R) scores over time, their evolving behavioural abilities could indicate a forthcoming diagnostic improvement with the Coma Recovery Scale-Revised (CRS-R). Forty-three Vegetative State / Unresponsive Wakefulness Syndrome (VS/UWS) patients were enrolled in the study. The patients were assessed weekly using the CRS-R and NCS(-R) for four consecutive weeks. The first assessment was within ten days after hospitalization. The assessments were performed between 09:30 and 11:30 AM in a room with constant levels of humidity, light and temperature, as well as an absence of transient noise. Noxious stimuli were administered using a Newton-meter, with pressure applied to the fingernail bed for a maximum of 5 seconds unless interrupted by a behavioral response from subjects. Seventeen patients demonstrated improvements in their level of consciousness, 13 of whom showed significant behavioral changes through the NCS(-R) before being diagnosed with a Minimally Conscious State (MCS) according to the CRS-R. The behavioral changes observed using the NCS(-R) corresponded to a high probability of observing an improvement from VS/UWS to MCS. To characterize the increased likelihood of this transition, our results present threshold scores of ≥5 for the NCS (accuracy 86%, sensitivity 87% and specificity 86%) and ≥3 for the NCS-R (accuracy 77%, sensitivity 89% and specificity 73%). In conclusion, a careful evaluation of responses to nociceptive stimuli in DOC patients could constitute an effective procedure in assessing their evolving conscious state.